Rendimento e qualidade de sementes de arroz irrigado em função da adubação com boro - Leite, Ricardo Figueiredo Cavalheiro (2008)
Boron is an essential plant nutrient. Its functions are related to cellular growth and flower development. At flowering, the micronutrient deficiency reduces male-fertility due to damage to microsporogenesis and to the pollen tube growth. This work aims to define the phases of higher sensibility of the culture, with the purpose of identifying appropriate times for applying of boron to the rice crop. Boron application, in form of sodium borate (Na2B4O7.10H2O), in dosage of 10 kg.ha, was made in five different phases: base fertilization; tillering; primary flower differentiation; booting stage; and full flowering. Evaluation on yield, sterility and rice yield components, as well as physiological quality of the seeds produced have been done. The results allowed the verification that the amount of sodium borate applied is not harmful to the flooded rice crop, and there are no effects of application of the nutrient in different times of cultivation.